Histological Evidence of Muscle Degeneration in Advanced Human Rotator Cuff Disease. (1st February 2017) - Gibbons, Michael C.; Singh, Anshu; Anakwenze, Oke; Cheng, Timothy; Pomerantz, Maxwill; Schenk, Simon; Engler, Adam J.; Ward, Samuel R.
Abstract : Background: Cellular remodeling in rotator cuff muscles following a massive rotator cuff tear is poorly understood. The aim of the current study was to provide histological evidence to elucidate the mode of muscle loss in advanced human rotator cuff disease and to assess tissue-level changes in relation to findings on noninvasive imaging. Methods: Rotator cuff muscle biopsy samples were taken from the scapular fossae from 23 consecutive patients undergoing reverse total shoulder arthroplasty in order to evaluate muscle composition in severe rotator cuff disease. Markers of vascularity; inflammation; fat distribution; and muscle atrophy, degeneration, and regeneration were quantified. Results: The samples primarily consisted of dense, organized connective tissue (48.2% ± 19.1%) and disorganized, loose connective tissue (36.9% ± 15.9%), with substantially smaller fractions of muscle (10.4% ± 22.0%) and fat (6.5% ± 11.6%). Only 25.8% of the biopsy pool contained any muscle fibers at all. Increased inflammatory cell counts (111.3 ± 81.5 macrophages/mm 2 ) and increased vascularization (66.6 ± 38.0 vessels/mm 2 ) were observed across biopsies. Muscle fiber degeneration was observed in 90.0% ± 15.6% of observable muscle fascicles, and the percentage of centrally nucleated muscle fibers was pathologically elevated (11.3% ± 6.3%). Fat accumulation was noted in both perifascicular (60.7% ± 41.4%) and intrafascicular (42.2% ± 33.6%) spaces, with evidence that lipid may replace contractile elements without altering muscle organization. Conclusions: Dramatic degeneration and inflammation of the rotator cuff muscles are characteristics of the most chronic and severe rotator cuff disease states, suggesting that muscle loss is more complicated than, and distinct from, the simple atrophy found in less severe cases. Clinical Relevance: In order to address degenerative muscle loss, alternative therapeutic approaches directed at muscle regeneration must be considered if muscle function is to be restored in late-stage rotator cuff disease.